Pengembangan Media Pembelajaran Matematika Berbasis Android untuk Tingkat SMP - Eka Septiyani; M Tohimin Apriyanto (JKPM (Jurnal Kajian Pendidikan Matematika), 2019)
This research is to develop android-based mathematics learning media for the junior high school level. This research was conducted at MTs Al-Wathoniyah 08. The research model used to develop this media was the ADDIE model. In this research, the product was tested on one media expert, one material expert, one linguist and a field trial. From the overall average value obtained from the validator, the expert teachers and students obtained a mean score of 3.65, which includes the category "Very Eligible". Formative evaluation results from media experts obtained a mean score of 3.8 which included the category "Very Eligible". Formative evaluation results from material experts obtained a mean score of 3.65, which includes the category "Very Eligible". Formative evaluation results from linguists obtained a mean score of 3.6 which falls into the "Very Eligible" category. The results of field evaluations from mathematics subject teachers obtained a mean score of 3.65 which falls into the "Very Eligible" category. And the results of student responses to the Android-based mathematics learning media obtained a mean score of 3.57 which belongs to the "Very Eligible" category. It can be concluded that the learning media developed "Very Worthy" is used in the learning process.